Solar powered UAV with remote monitoring and thermal imaging system for transmission line inspection - van Jaarsveld, Maarten; Du Toit, Brandon; N.Jiya, Immanuel; Gouws, Rupert (International Journal of Engineering and Technology, 2019)
Eskom, South Africaâ€™s electricity utility organisation, dedicates an enormous amount of resources in the form of time and money to visually inspect the conditions of these transmission lines on an annual basis. These transmission lines are inspected normally by means of a foot patrol or by flying a helicopter in close proximity to the line. During the foot patrol inspection, a team of people walk from pylon to pylon and inspect the transmission line. Binoculars and IR or corona detection cameras are typically used to aid their inspection. The transmission lines are often located in geographical areas where it is difficult to access these lines by foot; it then becomes necessary to use a helicopter to inspect the line. Various hazards exist in operating a helicopter in such close proximity to these transmission lines and the process of hiring or employing trained specialists to operate the helicopter and the accompanying equipment is costly. Inspecting transmission lines by means of foot patrols or by helicopter is not only costly, but dangerous as well. This paper proposes a new method of transmission line inspection using a solar powered UAV with the inspection equipment mounted on it. The addition of the solar cells to the UAV was beneficial to the overall flight performance of the aircraft, only contributing 6% to the aircrafts total weight, while supplying 20% to 35% of the aircrafts energy needs. This resulted in an approximate increase in the flight range of the aircraft by about 20%.Â Â